Sustainable future : trends, strategies and development : proceedings of the 3rd Conference on Managing Digital Industry, Technology and Entrepreneurship, (CoMDITE 2022), Bandung, Indonesia, 24 May 2022 /: trends, strategies and development : proceedings of the 3rd Conference on Managing Digital Industry, Technology and Entrepreneurship, (CoMDITE 2022), Bandung, Indonesia, 24 May 2022. (2022) - Unknown
No abstract available